2022
DOI: 10.3389/fneur.2022.891531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of docosahexaenoic acid and eicosapentaoic acid supplementation on white matter integrity after repetitive sub-concussive head impacts during American football: Exploratory neuroimaging findings from a pilot RCT

Abstract: and Brinton RD ( ) E ects of docosahexaenoic acid and eicosapentaoic acid supplementation on white matter integrity after repetitive sub-concussive head impacts during American football: Exploratory neuroimaging findings from a pilot RCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…In collegiate American football players, higher RBC omega-3 status from omega-3 (DHA + EPA) supplementation blunts a rise in blood neurofilament light (NfL) concentrations, a sensitive blood biomarker for brain injury, throughout a competitive season of repetitive helmet impacts (Heileson et al, 2021). In addition, higher RBC omega-3 status in American football players improves brain functional connectivity (Raikes et al, 2022). These findings highlight the importance of higher RBC omega-3 status for player brain health in contact sports populations exposed to repeated head impacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In collegiate American football players, higher RBC omega-3 status from omega-3 (DHA + EPA) supplementation blunts a rise in blood neurofilament light (NfL) concentrations, a sensitive blood biomarker for brain injury, throughout a competitive season of repetitive helmet impacts (Heileson et al, 2021). In addition, higher RBC omega-3 status in American football players improves brain functional connectivity (Raikes et al, 2022). These findings highlight the importance of higher RBC omega-3 status for player brain health in contact sports populations exposed to repeated head impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Omega-3 polyunsaturated fatty acids (PUFAs), docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA) have anti-inflammatory properties (Gabbs et al, 2015). These properties are potentially neuroprotective against brain injury from repeated head impacts in contact sports populations (Heileson et al, 2021; Raikes et al, 2022). When the brain is mechanically injured, omega-3s are released from neuronal membranes and metabolized to help reduce inflammation and promote injury recovery (Dyall, 2015; Lust et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found a moderately strong inverse correlation between the change in serum Nf-L and the change in %DHA + EPA. Finally, a subgroup analysis from Mullins and colleagues included neuroimaging that showed stronger structural and functional connectivity of the brain in American football players who supplemented with DHA + EPA compared to placebo, despite notable white matter damage [81]. Of note, Miller et al recently determined that subjects supplied with 2000 mg DHA per day were symptom-free 5 days faster and were cleared for return to play 5.5 days faster compared to placebo following a diagnosed mTBI [82].…”
Section: Epa and Dha For Athletes' Healthmentioning
confidence: 99%